Pengaruh bahan isian terhadap kekuatan geser Adhesive melalui uji geserLap tunggal. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Kawasan dan Pedesaan Universitas Gadjah Mada, 1999)
ABSTRAK The objective of this research is to investigate an adhesive joint that has been improved its bondline thickness using filler material. The adhesives used in this research were FM-73 and AF-163, which were added cerex as filler. The specimens sheared tested according to ASTM D1002 standard. The results show that two layers cerex can increase the adhesive bondline thickness until 88%. Furthermore the adhesive with filler material has similar strength with the adhesive without one.